SOCIAL MEDIA INFLUENCER SEBAGAI INSTRUMEN PROMOSI PROGRAM STUDI BARU - Difi Dahliana; Annisa Mahfuzah; Fahruddin Fahruddin; Muhammad Noval; Rimayanti Rimayanti; Nurhafiyanisa Nurhafiyanisa; Hafizah Aziza; Irsyad Khoiri (JEMMA (Journal of Economic, Management and Accounting), 2024)
Along with the popularity of social media influencers as a promotional tool in digital marketing, the Faculty of Economics and Islamic Business (FEBI) UIN Antasari Banjarmasin promotes new study programs through social media influencer services to attract prospective new students in the 2023/2024 admissions. The effectiveness of social media influencers needs to be measured. However, measurements of the effectiveness of social media influencers in promoting the new FEBI UIN Antasari study program have never been carried out. For this reason, this study aims to measure the effectiveness. The design of this study is quantitative research, with engagement rate, conversion rate, and mini-survey approaches, where data analysis is carried out with percentage descriptive techniques.Â  This research found that influencer social media accounts are not an effective medium to promote study programs compared to the official websites and social media accounts of universities themselves. This finding contributes to consideration in formulating promotional strategies for new student admissions in the future.